Elucidation of the Mechanism of Resistance Development of Colletotrichum horii Causing Persimmon Anthracnose to Tebuconazole - Eunsol Yeon; Seongho Choi; Heung Tae Kim (Research in Plant Disease)
To elucidate the mechanism of resistance to tebuconazole in Colletotrichum horii, the effects of tebuconazole on the ergosterol biosynthetic process and the CYP51 gene of C. horii were investigated in this study. By treating tebuconazole, ergosterol biosynthesis was inhibited in both susceptible and resistant isolate of C. horii 15GKYD4 and 15GKNJ1. To analyze the DNA sequence of CYP51 gene, the gene was amplified by PCR with CG-cyp14aF/CG-cyp14R primer from 40 and 33 isolates of C. horii sensitive and resistant to tebuconazole, respectively. There were no point mutations in the CYP51 gene of any isolates. However, there were differences in the expression levels of the CYP51 gene. The CYP51 gene expression levels of susceptible isolates were 1.1–5.5 fold when not treated with tebuconazole, and remained 1.7–3.9 fold after tebuconazole treatment. However, in resistant isolates, the expression levels, which were 4.0–5.3 hold in the untreated control, increased to 16.0–25.9 times after tebuconazole treatment. The expression levels of the CYP51 gene in resistant isolates were highest 2.5 hr after tebuconazole treatment. Based on the results of this study, the overexpression of CYP51 gene is illustrated as the mechanism of resistance of C. horii to tebuconazole. It is believed that these results can be used as important basic information for managing fungicide resistance in the field.